2004
DOI: 10.1038/sj.npp.1300547
|View full text |Cite
|
Sign up to set email alerts
|

Activation of D1, but not D2 Receptors Potentiates Dizocilpine-Mediated Disruption of Prepulse Inhibition of the Startle

Abstract: Although substantial evidence has shown interactions between glutamatergic and dopaminergic systems play a cardinal role in the regulation of attentional processes, their involvement in informational filtering has been poorly investigated. Chiefly, little research has focused on functional correlations between the dopaminergic system and the mechanism of action of N-methyl-D-aspartate (NMDA) receptor antagonists on sensorimotor gating. The present study was targeted at evaluating whether the activation of D 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 65 publications
3
25
3
Order By: Relevance
“…These effects resulted in a significant amphetamine×pyrilamine interaction (p<0.025) pyrilamine did not have a significant main effect on the PPI magnitude in Experiment 1, but was able to attenuate the amphetamine-induced PPI disruption. Pyrilamine reduced the startle response magnitude in startle-alone trials, an outcome similar to findings reported in some earlier studies with clozapine (Bortolato et al 2005;Bubenikova et al 2005;Conti et al 2005), though other reports show no significant changes on the startle amplitude with clozapine (Caceda et al 2005;Tenn et al 2005). Still, it is believed that the results of antipsychotics on PPI are independent of their effects on the startle response magnitude (Johansson et al 1995).…”
Section: Ketanserin Interactions With Amphetamine-induced Ppi Impairmsupporting
confidence: 67%
See 1 more Smart Citation
“…These effects resulted in a significant amphetamine×pyrilamine interaction (p<0.025) pyrilamine did not have a significant main effect on the PPI magnitude in Experiment 1, but was able to attenuate the amphetamine-induced PPI disruption. Pyrilamine reduced the startle response magnitude in startle-alone trials, an outcome similar to findings reported in some earlier studies with clozapine (Bortolato et al 2005;Bubenikova et al 2005;Conti et al 2005), though other reports show no significant changes on the startle amplitude with clozapine (Caceda et al 2005;Tenn et al 2005). Still, it is believed that the results of antipsychotics on PPI are independent of their effects on the startle response magnitude (Johansson et al 1995).…”
Section: Ketanserin Interactions With Amphetamine-induced Ppi Impairmsupporting
confidence: 67%
“…Different experimental methods to induce PPI deficits in rats include the stimulation of dopamine receptors, activation of serotonin systems, blockade of N-methyl D-aspartate (NMDA) receptors, and developmental manipulations such as isolated rearing (for a complete review of different models of PPI disruption and the effects of various pharmacological manipulations, see Geyer et al 2001). For instance, the NMDA glutamate receptor antagonist dizocilpine robustly disrupts PPI in rats (Mansbach and Geyer 1989), and the antipsychotic clozapine has been show to reverse that disruption (Bakshi et al 1994;Bubenikova et al 2005;Bortolato et al 2005;Caceda et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…However, some of the effects of NMDA receptor antagonism involve changes in dopamine release and dopamine receptor activation in the nucleus accumbens. For example, stimulation of dopamine D1 receptors, but not D2 receptors, potentiates the disruption of PPI caused by treatment with MK-801 in rats (Bortolato et al 2005). Unlike the effect of apomorphine, this interaction is apparently not influenced by G z .…”
Section: Discussionmentioning
confidence: 95%
“…Dizocilpine induces popping plausibly through a dopaminergic mechanism, since haloperidol is able to reverse this behavior in a dose-dependent manner (Deutsch and Hitri, 1993). In contrast, the weight of evidence supports the idea that dizocilpine-mediated PPI disruption is mainly independent by dopaminergic mechanisms, although it might be potentiated by acute D 1 receptor activation (Bortolato et al, 2005) or blunted by chronic D 2 agonist treatment (Krupin and Hammer, 2005). Indeed, atypical, but not typical antipsychotics, are able to attenuate dizocilpine-induced PPI deficits , suggesting that D 2 receptors are not critically involved in the psychotomimetic mechanisms of NMDA receptor antagonists.…”
Section: Effects Of Tpm On Apomorphine-induced Ppi Disruptionmentioning
confidence: 98%